Deoxythymidylate Kinase as a Promising Marker for Predicting Prognosis and Immune Cell Infiltration of Pan-cancer - Lan, Tianfeng; Wang, Yachao; Miao, Jinxin; Guo, Haoran; Wang, Zheng; Wang, Jianyao; Zhang, Chunyang; Yang, Panpan; Zhang, Zhongxian; Dunmall, Louisa Chard; Wang, Yaohe (Frontiers in Molecular Biosciences, 2022)
Background: Deoxythymidylate kinase (DTYMK) serves as a pyrimidine metabolic rate-limiting enzyme that catalyzes deoxythymidine monophosphate (dTMP) to generate deoxythymidine diphosphate (dTDP). It remains unclear whether DTYMK expression has the potential to predict outcome and immune cell infiltration in cancers. Methods: DTYMK expression profile was analyzed using Oncomine, TIMER, GEPIA and UALCAN databases. The influence of DTYMK on immune infiltration was examined using TIMER and TISIDB databases. DTYMK interactive gene hub and co-expressing genes were obtained and analyzed by STRING and Linkedomics, respectively. The relationship between DTYMK expression and patient prognosis was validated using GEPIA, Kaplan-Meier plotter, and PrognoScan databases.The functions of DTYMK in cancer cells were also biologically validated in vitro. Results: DTYMK expression was elevated in tumor tissues compared with their control counterparts. DTYMK expression varied in different stages and discriminatorily distributed in different immune and molecular subtypes. Higher expression of DTYMK predicted worse outcome in several cancer types such as liver hepatocellular carcinoma (LIHC) and lung adenocarcinoma (LUAD). High DTYMK expression was positively or negatively correlated with immune cell infiltration, including B cell, CD8+ cell, CD4+ T cell, macrophage, neutrophil and dendritic cell, depending on the type of cancers. Additionally, DTYMK co-expressing genes participated in pyrimidine metabolism as well as in T helper cell differentiation in LIHC and LUAD. In vitro, knockdown of DTYMK suppressed cell migration of liver and lung cancer cells. Conclusion: DTYMK might be taken as an useful prognostic and immunological marker in cancers and further investigation is warrented.